Determination of the minimum fully protective dose of adenovirus-based DIVA vaccine against peste des petits ruminants virus challenge in East African goats. (December 2016) - Holzer, Barbara; Taylor, Geraldine; Rajko-Nenow, Paulina; Hodgson, Sophia; Okoth, Edward; Herbert, Rebecca; Toye, Philip; Baron, Michael
Abstract Peste des petits ruminants virus (PPRV) causes an economically important disease of sheep and goats, primarily in developing countries. It is becoming the object of intensive international control efforts. Current vaccines do not allow vaccinated and infected animals to be distinguished (no DIVA capability). We have previously shown that recombinant, replication-defective, adenovirus expressing the PPRV H glycoprotein (AdH) gives full protection against wild type PPRV challenge. We have now tested lower doses of the vaccine, as well as AdH in combination with a similar construct expressing the PPRV F glycoprotein (AdF). We show here that, in a local breed of goat in a country where PPR disease is common (Kenya), as little as 107 pfu of AdH gives significant protection against PPRV challenge, while a vaccine consisting of 108 pfu of each of AdH and AdF gives apparently sterile protection. These findings underline the utility of these constructs as DIVA vaccines for use in PPR control.